Effect of the Nano-Silica Addition on the Mechanical Properties of Polymer Concrete - Septriansyah, Verinazul; Saloma; Nurjannah, Siti Aisyah; Saggaff, Anis; Usman, Arie Putra; Ngian, Shek Poi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The latest advances in science and technology have positioned nanomaterials at the vanguard of contemporary research. Nano silica (SiO2) is an illustrative example of a nanomaterial extensively utilized in concrete manufacturing due to its properties as a pozzolan. The objective of this study is to elucidate the characteristics of nano silica and its effect on the performance of polymer concrete through experimental methods. X-ray diffraction (XRD) tests indicate that nano silica exhibits a high amorphous phase. Consequently, nano silica enhances the C-S-H gel formation reaction, producing more robust and denser specimens. The maximum compressive strength reached 45.23 MPa when adding 0.4% nano-silica with a specific gravity of 1573.33 kg/m3. For comparison, concrete without nano silica had a maximum compressive strength of 40.05 MPa with a particular gravity of 1610.67 kg/m3. Observation using a scanning electron microscope (SEM) showed that the nano-silica mixture exhibited excellent particle distribution as an activating agent that could enhance the strength of the specimens. Nevertheless, the observed reduction in compressive strength might be affected by several factors, including particle clusters and the presence of compounds carried by the fine aggregates that influence the mechanical properties of polymer concrete. Integrating nano-silica is pivotal in enhancing the compressive strength and reducing the specific gravity of polymer concrete specimens. The increased strength and decreased specific gravity render nano silica a promising additive for polymer concrete applications.